Evaluation of cardiac parameters and other safety outcomes of brolucizumab treatment in patients with neovascular age‐related macular degeneration - Nadia Zakaria; Nicolas Guerard; Andres Emanuelli; Pravin Dugel; Jen Watts; Melissa Liew; Margarita Gekkieva; Markus Hinder (Wiley, 2022)
Abstract This was a prospective, single‐dose, single‐arm, open‐label, non‐randomized, multicenter clinical study to determine cardiovascular safety after a single brolucizumab 6 mg intravitreal injection in neovascular age‐related macular degeneration patients (N = 14). Electrocardiogram (ECG) data were collected at different time points using 12‐lead Holter and standard ECG, and patients were followed up to 8 days (end of study) for any signs of ocular and non‐ocular adverse events (AEs). No clinically meaningful changes were observed in cardiac parameters. No patient had a ≥30 msec change from baseline in heart rate-corrected QT using Fridericia's formula (QTcF), and no patient had a new QTcF value of ≥450 msec between 20 and 24 h after treatment. No deaths or serious AEs were reported during the study period. These results are in line with the absence of new cardiovascular safety signal based on the ECG recordings collected over the first year of the pivotal studies performed with brolucizumab in DME. Trial Registration: ClinicalTrials.gov identifier: NCT03954626.